PROBLEM BASED LEARNING UNTUK PENINGKATAN HASIL BELAJAR IPS SISWA KELAS IV SDN 08 MARUNGGI KOTA PARIAMAN - Sumarni Sumarni (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2017)
This study is encouraged by the low learning achievement of students grade IV SDN 08 Marunggi in social subject. This study is aimed to improve students’ learning achievement in social subject through implementation of problem based learning model. This is a classroom action research with 32 students of grade IV at SDN 08 Marunggi as the subjects. Instruments of this study include observation sheet of teacher and cognitive test for students. Result of this study shows that students’ cognitive ability for knowledge level increase from 68.18 in cycle I to 76.49 in cycle II. Meanwhile, students’ cognitive ability for understanding level increase from 75.97 in cycle I to 90.15 in cycle II. Hence, problem based learning model can improve students’ learning achievement in social subject.